PENGARUH KOMPETENSI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR - Sulistiani Syafitri; Mappasila, Moh. Suaib; Alam, Ryan Saputra; Nurfai Al Faisal (Scientium Management Review, 2025)
The purpose of this study is to examine the effect of competence on Organizational Citizenship Behavior (OCB). This research employs a quantitative analysis with a population consisting of the whole employees in the unit of the state-owned electricity company. The data analysis method used is Partial Least Squares (PLS). The results of this study indicate that competence has a positive effect on Organizational Citizenship Behavior (OCB).